European jobs and skills : a comprehensive review 2015 ; report - Colebrook, Catherine [Verfasser]; Cory, Giselle [Verfasser]; Dolphin, Tony [Verfasser]; Doyle, Patrick [Verfasser]; Carney Fox, Diana [Verfasser]; Hatfield, Izzy [Verfasser]; McNeil, Clare [Verfasser]; Pontin, Graham [Verfasser]; Stirling, Alfie [Verfasser] (My University, 2015)
"This second annual European Jobs and Skills review examines trends in employment and skills development across the EU28, and in Europe’s five biggest economies: Germany, the UK, France, Spain and Italy. It assesses how effective policy has been to date at boosting employment and skills, and identifies the key labour market weaknesses that firms and policymakers need to address in the coming years." (Editor ; BIBB-Doku)
Keywords: G 2.3.4 Qualifikationswandel; G 1.2 Arbeitsmarkt; Beschäftigungspolitik; Arbeitsmarktentwicklung; Digitalisierung; Qualifikationsbedarf; Arbeitsmarktanalyse; Kompetenzentwicklung; Unterbeschäftigung; Internationaler Vergleich; Europa; Bundesrepublik Deutschland; Großbritannien; Frankreich; Spanien; Italien